2011
DOI: 10.1007/s10856-011-4507-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanocomposite coating for dental implant applications in vitro and in vivo evaluation

Abstract: This study aimed at preparation and in vitro and in vivo evaluation of novel bioactive, biodegradable, and antibacterial nanocomposite coating for the improvement of stem cells attachment and antibacterial activity as a candidate for dental implant applications. Poly (lactide-co-glycolide)/bioactive glass/hydroxyapatite (PBGHA) nanocomposite coating was prepared via solvent casting process. The nanoparticle amounts of 10, 15, and 20 weight percent (wt%) were chosen in order to determine the optimum amount of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 42 publications
2
19
0
1
Order By: Relevance
“…As a consequence, the presence of 45SBG nanoparticle in the nancomposite construct and their ionic products released from them in medium could induce cell proliferation. This results have compliances with several publications [11,12]. Furthermore, from the other point of view, the presence of Ha and fibrin could promotecell attachment, viability, and proliferation.…”
Section: 3viability and Proliferation Of The Hadmscs On The Preparsupporting
confidence: 92%
See 4 more Smart Citations
“…As a consequence, the presence of 45SBG nanoparticle in the nancomposite construct and their ionic products released from them in medium could induce cell proliferation. This results have compliances with several publications [11,12]. Furthermore, from the other point of view, the presence of Ha and fibrin could promotecell attachment, viability, and proliferation.…”
Section: 3viability and Proliferation Of The Hadmscs On The Preparsupporting
confidence: 92%
“…%) displayed a slightly increase of pH in the early days of incubation time and then decreasing around 7 after 28 days.Literatureshave reported that overloading contents of BG (up to 30 wt. %) could accelerate the degradation rate of nanocomposite scaffolds [33,11]. Furthermore, in this work it was demonstrated that the nanocomposite scaffolds with 25 wt.…”
Section: In Vitro Biodegradation Properties Of the Scaffoldsmentioning
confidence: 64%
See 3 more Smart Citations